Single‐cell RNA‐seq describes the transcriptome landscape and identifies critical transcription factors in the leaf blade of the allotetraploid peanut (Arachis hypogaea L.). Issue 11 (19th July 2021) - Liu, Hao; Hu, Dongxiu; Du, Puxuan; Wang, Liping; Liang, Xuanqiang; Li, Haifen; Lu, Qing; Li, Shaoxiong; Liu, Haiyan; Chen, Xiaoping; Varshney, Rajeev K; Hong, Yanbin
Summary: Single‐cell RNA‐seq (scRNA‐seq) has been highlighted as a powerful tool for the description of human cell transcriptome, but the technology has not been broadly applied in plant cells. Herein, we describe the successful development of a robust protoplast cell isolation system in the peanut leaf. A total of 6, 815 single cells were divided into eight cell clusters based on reported marker genes by applying scRNA‐seq. Further, a pseudo‐time analysis was used to describe the developmental trajectory and interaction network of transcription factors (TFs) of distinct cell types during leaf growth. The trajectory enabled re‐investigation of the primordium‐driven development processes of the mesophyll and epidermis. These results suggest that palisade cells likely differentiate into spongy cells, while the epidermal cells originated earlier than the primordium. Subsequently, the developed method integrated multiple technologies to efficiently validate the scRNA‐seq result in a homogenous cell population. The expression levels of several TFs were strongly correlated with epidermal ontogeny in accordance with obtained scRNA‐seq values. Additionally, peanut AHL23 ( AT‐HOOK MOTIF NUCLEAR LOCALIZED PROTEIN 23 ), which is localized in nucleus, promoted leaf growth when ectopically expressed in Arabidopsis by modulating the phytohormone pathway. Together, our study displays that application of scRNA‐seq can provide new hypotheses regarding cell differentiation in the leaf blade of Arachis hypogaea . We believe that this approach will enable significant advances in the functional study of leaf blade cells in the allotetraploid peanut and other plant species.